The education of nations : how the political organization of the poor, not democracy, led governments to invest in mass education - Kosack, Stephen, 1978- (Oxford : Oxford University Press, 2012)
What causes a government to invest - or not invest - in poor citizens, especially mass education? In this book, Stephen Kosack focuses on three radically different developing countries whose developmental trajectories bear little resemblance to each other and offers an elegant and pragmatic answer to this question.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on July 13, 2012).
Keywords: Education and state -- Developing countries -- Cross-cultural studies; Education -- Economic aspects -- Developing countries -- Cross-cultural studies; Poor -- Education -- Developing countries -- Cross-cultural studies